2018
DOI: 10.1097/md.0000000000010229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous lidocaine infusion on long-term postoperative pain after spinal fusion surgery

Abstract: Background:Intravenous lidocaine infusion is known to reduce postoperative pain for days or weeks beyond the infusion time, and plasma half-life in several types of surgical procedures.Objectives:To evaluate the effect of intravenous (IV) lidocaine infusion on long term postoperative pain intensity for 3 months in patients undergoing spinal fusion surgery.Study Design:Prospective randomized, double-blinded study.Setting:Assiut University Hospital, Assiut, Egypt.Methods:Forty patients undergoing spinal fusion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 26 publications
(31 reference statements)
4
33
0
1
Order By: Relevance
“…To observe postoperative earlier analgesic effect of intravenous lidocaine, another advantage of remifentanil is its ability to avoid interference of using other opioid drugs. Administration of intravenous lidocaine was shown to have an opioid sparing effect during GA, including fentanyl [16], sufentanil [17] and morphine [18]. In a recent study, the remifentanil sparing effect of intravenous lidocaine in the intraoperative period was found [19], which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…To observe postoperative earlier analgesic effect of intravenous lidocaine, another advantage of remifentanil is its ability to avoid interference of using other opioid drugs. Administration of intravenous lidocaine was shown to have an opioid sparing effect during GA, including fentanyl [16], sufentanil [17] and morphine [18]. In a recent study, the remifentanil sparing effect of intravenous lidocaine in the intraoperative period was found [19], which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…In both adjusted and unadjusted analyses, IVL was not significantly associated with opioid use during hospitalization or pain scores during admission hours 24-48. Our findings show conflicting evidence and only partially corroborate previous studies that showed an association between IVL use and decreased opioid utilization after various operations [18][19][20][21][22][23][24]. Notably these studies assessed opioid utilization at different time points after surgery, ranging from 6 hours to up to 72 hours [23,24].…”
Section: Discussionsupporting
confidence: 73%
“…However recent meta-analyzes suggest that lidocaine exerts a positive analgesic effect only in abdominal surgery [11,12]. Benefits of lidocaine usage in spine surgery in adults have not been thoroughly investigated yet [3,16,31,32]. The results of the few studies conducted in the adults population are ambiguous: Farag et al reported that i.v.…”
Section: Discussionmentioning
confidence: 99%
“…lidocaine significantly improved the postoperative analgesia, and patients undergoing complex spine surgery receiving lidocaine had significantly higher physical SF-12 scores, evaluated one month and three months after surgery than from the placebo group; there were no differences between the groups in PONV intensity and time of hospitalization [3]; Kim et al found that i.v. lidocaine decreased the severity of the postoperative pain, the consumption of opioids and reduced the length of hospital stay after microdiscectomy surgery [32]; Ibrahim et al reported that lidocaine significantly reduced hospitalization time and the postoperative pain for up to three months after spine fusion surgery [16]. Dewiter et al observed no effect of lidocaine on the postoperative pain severity, morphine requirements, PONV, the intensity of the postoperative inflammatory reaction, the hospitalization time and quality of life evaluated one month postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation